Efektivitas Model Blended Learning Pada Pembelajaran Tematik - Wahyu Lailatul Hikmah; Husniati Husniati; Safruddin Safruddin (Journal of Classroom Action Research, 2022)
This study aims to find out and describe the effectiveness of blended learning models in thematic learning in class V SDN 20 Ampenan during the Covid-19 pandemic. The type of research used is qualitative phenomenology. The data in this study is a description of the effectiveness of blended learning models on thematic learning, with the subset of principal research, and fifth-grade teachers. The research was conducted with interview techniques, and documentation and using data analysis techniques according to Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion withdrawal. The conclusion obtained from this study is, the blended learning model on thematic learning for Theme 5 healthy is important, Subtema 3, Learning 1, during the Covid-19 pandemic class V SDN 20 Ampenan School Year 2020/2021 remains effective, despite changes in learning time, use of learning media, and learning materials. The use of learning media is the use of online media applications for the learning process. In addition to the facilities that must be adequate, of course, teachers are more extra in providing understanding related to the material delivered to students during the online and face-to-face learning process that must be done optimally in a limited time, and conduct assessments as usual but with observations done online and face-to-face, so that learning continues to be good and effective even in the Covid-19 pandemic.